The Effect of Profitability, Firm Size and Capital Structure on Firm Value - Sukamdi, Irma (Dinasti International Journal of Digital Business Management, 2023)
Company value is an important thing that investors must know. Company value provides a separate view for investors on the ability of a company in an effort to provide maximum benefits to investors. Company values are subject to change at any time. The value of the company can be influenced by internal as well as external factors. This study aims to determine profitability, company size and capital structure to company value. For future research, this study will be useful to examine the influence between variables. The research library method, sourced from Mendeley, Google Scholar, and other academic online media is used to discuss how variables influence. The results of this literature review article are as follows: 1) profitability affects the value of the company; 2) the size of the company affects the value of the company; and 3) capital structure affects the value of the company.